Development of multimedia-based learning resources for islamic education subjects at sma sentosa bhakti baturaja - Sri Murni; Desi Oktariyanti; Herlina Herlina (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
The rapid development of digital technology demands innovation in education, including in Islamic Religious Education (PAI). This study aims to develop multimedia-based learning resources and analyze their effectiveness in improving PAI learning quality at SMA Sentosa Bhakti Baturaja. The research employed a Research and Development (R&D) design using Borg & Gall’s model, covering needs analysis, design, development, limited trials, revision, and field testing. The participants consisted of PAI teachers and students, with data collected through observation, interviews, questionnaires, and documentation. The findings indicate that the developed interactive multimedia successfully enhanced students’ motivation, interest, and learning outcomes. Moreover, the multimedia facilitated more participatory classroom interactions and helped students connect religious concepts with real-life contexts. This study highlights that multimedia integration in PAI not only strengthens cognitive learning but also fosters affective and psychomotor development. Therefore, the study provides practical implications for teachers in designing innovative learning resources and theoretical contributions to the discourse of technology-based Islamic education.